Circular Economy of Coal Fly Ash and Silica Geothermal for Green Geopolymer: Characteristic and Kinetic Study - Petrus, Himawan Tri Bayu Murti; Olvianas, Muhammad; Shafiyurrahman, Muhammad Faiz; Pratama, I Gusti Agung Arvin Nanda; Jenie, Siti Nurul Aisyiyah; Astuti, Widi; Nurpratama, Muhammad Istiawan; Ekaputri, Januarti Jaya; Anggara, Ferian (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The study of geopolymers has become an interesting concern for many scientists, especially in the infrastructure sector, due to having inherently environmentally friendly properties and fewer energy requirements in production processes. Geopolymer attracts many scientists to develop practical synthesis methods, useful in industrial-scale applications as supplementary material for concrete. This study investigates the geopolymerization of fly ash and geothermal silica-based dry activator. The dry activator was synthesized between NaOH and silica geothermal sludge through the calcination process. Then, the geopolymer mortar was produced by mixing the fly ash and dry activator with a 4:1 (wt./wt.) ratio. After mixing homogeneously and forming a paste, the casted paste moved on to the drying process, with temperature variations of 30, 60, and 90◦ C and curing times of 1, 3, 5, 7, 14, 21, 28 days. The compressive strength test was carried out at each curing time to determine the geopolymer’s strength evolution and simulate the reaction’s kinetics. In addition, ATR-FTIR spectroscopy was also used to observe aluminosilicate bonds’ formation. The higher the temperature, the higher the compressive strength value, reaching 22.7 MPa at 90◦ C. A Third-order model was found to have the highest R2 value of 0.92, with the collision frequency and activation energy values of 1.1171 day−1 and 3.8336 kJ/mol, respectively. The utilization of coal fly ash and silica geothermal sludge as a dry activator is, indeed, an approach to realize the circular economy in electrical power generations.